(untitled) (Indian Journal of Public Health Research & Development, 2022)
The objective of the study was to understand as well as to compare the psychosocio economic factors of families of two economic backgrounds with cerebral palsy child. It was a mixed method exploratory sequential design. The qualitative data was obtained from 08 parents each from monthly income Rs 10000/ and below (gr1), and monthly income Rs 30 000 and above (gr2) Quantitative data was obtained from 121 group 1 and 101 from group 2 families. The mean age of cp children was not statistically significant. 89% of group 1 belong to upper lower SES where as 67% of group 2 belonged to upper middle class. Social interaction was significantly more affected in group 1. Even these subjects were significantly more depressed. The social support was observed to be from maternal side in both the groups. There was significant difference on expenditure of the child. There was no significant difference in early intervention pattern. The groups were aware about therapy from community rather than clinicians.